2003
DOI: 10.1038/ncb1053
|View full text |Cite
|
Sign up to set email alerts
|

Stable reprogrammed heterokaryons form spontaneously in Purkinje neurons after bone marrow transplant

Abstract: Heterokaryons are the product of cell fusion without subsequent nuclear or chromosome loss. Decades of research using Sendai-virus or polyethylene glycol (PEG)-mediated fusion in tissue culture showed that the terminally differentiated state of a cell could be altered. But whether stable non-dividing heterokaryons could occur in animals has remained unclear. Here, we show that green fluorescent protein (GFP)-positive bone-marrow-derived cells (BMDCs) contribute to adult mouse Purkinje neurons through cell fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
321
3
16

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 423 publications
(360 citation statements)
references
References 39 publications
20
321
3
16
Order By: Relevance
“…Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects. Here we report that chronic inflammation resulting from severe dermatitis or autoimmune encephalitis leads to robust fusion of BMDCs with Purkinje neurons and formation of hundreds of binucleate heterokaryons, a 10-100 fold higher frequency than previously reported 8,10,11,14 . Single haematopoietic stem cell transplants showed that the fusogenic cell is in the haematopoietic lineage and parabiosis experiments revealed that fusion can occur without irradiation.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects. Here we report that chronic inflammation resulting from severe dermatitis or autoimmune encephalitis leads to robust fusion of BMDCs with Purkinje neurons and formation of hundreds of binucleate heterokaryons, a 10-100 fold higher frequency than previously reported 8,10,11,14 . Single haematopoietic stem cell transplants showed that the fusogenic cell is in the haematopoietic lineage and parabiosis experiments revealed that fusion can occur without irradiation.…”
mentioning
confidence: 59%
“…
AbstractTransplanted bone marrow derived cells (BMDCs) have been reported to fuse with cells of diverse tissues [1][2][3][4][5][6][7][8][9][10][11][12][13] , but the extremely low frequency of fusion has led to the view that such events are biologically insignificant. Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects.
…”
mentioning
confidence: 99%
See 3 more Smart Citations